Two Cases of Late-Onset Anti-NMDAr Auto-Immune Encephalitis After Herpes Simplex Virus 1 Encephalitis - Guillaume Dorcet; Marie Benaiteau; Chloé Bost; Chloé Bost; Catherine Mengelle; Fabrice Bonneville; Fabrice Bonneville; Guillaume Martin-Blondel; Guillaume Martin-Blondel; Jérémie Pariente; Jérémie Pariente (Frontiers in Neurology, 2020)
Context: Encephalitis due to herpes simplex virus 1 (HSV-1) was described as a potential trigger for the development of anti-N-methyl-D-aspartate receptor (NMDAr) auto-immune encephalitis (AIE) within a few days to a few weeks after the infection.Methods: We assessed clinical, radiological, and biological diagnoses process, treatment response, and evolution.Cases Reported: We report here cases of a 71-year-old man and a 57-year-old woman presenting anti-NMDAr AIE, respectively, 12 and 7 months after HSV-1 encephalitis. In both cases, the onset was brisk, and the symptoms were mainly neuropsychiatric (paranoid delirium, Capgras, and Cotard syndromes) and cognitive, with anterograde amnesia. Relapse of HSV encephalitis, epilepsy, and paraneoplastic neurologic syndromes were excluded. The clinical response to first-line treatments composed of intravenous immunoglobulins and high-dose corticosteroids was poor, whereas significant improvement was noticed after rituximab induction.Conclusion: Post-herpetic anti-NMDAr AIE could arise several months after infection. Clinicians must be aware of this possibility, particularly if cognitive and/or psychiatric symptoms occurred after a remitting period. In our two cases, only rituximab was associated with clinical improvement.